The value of victory in Pindar's odes - Boeke, Hanna (Brill, 2007)
Preliminary material /Boeke – Chapter One. Introduction /Boeke – Chapter Two. Gnomai as a source of cosmological reflection /Boeke – Chapter Three. The gnomic expression of cosmology in Pindar /Boeke – Chapter Four. Cosmology in action: An analysis of selected odes /Boeke – Chapter Five. The poet as mediator of cosmology /Boeke – Chapter Six. Conclusion /Boeke – Bibliography /Boeke – General index /Boeke – Index of passages cited /Boeke – Copyright page /Boeke. This book investigates the cosmological context of Pindar’s victory odes, and how it influences his presentation of praise. The study first focuses on gnomai as a reflection of cosmology, using these sayings to establish the views the poems reveal on matters such as the divine, the human condition and man in society. This overview is complemented by detailed literary analyses demonstrating how cosmology functions in individual odes. They show that Pindar shapes the poet persona to emphasize different aspects of the traditional world view or represent varying viewpoints so that he can praise each victor according to his particular circumstances. By focusing on cosmology the book highlights a neglected dimension of Pindar’s odes and challenges some traditional views on this poet
10.1163/ej.9789004158481.i-230
Keywords: Pindar; PÍndaro; PÍndaro - Ca. 518-438 A.C; Cosmology; Ancient; in literature; Praise in literature; Literatura grega clássica; Poesia lírica